Comparative Analysis of Verbs of Motion in Uzbek and English Languages - Boboyarova D.F. (Zien Journals, 2023)
This article discusses the semantic issues of verbs of motion in English and Uzbek languages. At the same time, a comparative analysis of the verb of motion of the English and Uzbek languages is carried out in the space of a particularly relevant microfield, which specifically indicates the semantic parameters of the verbs of motion, as well as involving the application of a variety of methods of linguistic analysis.
Keywords: Semantics of verbs; verbs of motion; verbs of the English language